Comparison of the acute stress response in southern white rhinoceros (Ceratotherium simum simum) immobilised with four different drug protocols - Hooijberg, Emma Henriette (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.